The Relationship between Time Management and Academic Procrastination in Students Who Participate in Organizations - Osin Oktariani; Triave Nuzila Zahri; Zadrian Ardi; Lisa Putriani (Jurnal Aplikasi IPTEK Indonesia, 2024)
This research is motivated by the fact that many students who are administrators of organizations are lazy to do their assignments so they procrastinate and are not able to manage their time well. This study aims to describe time management and academic procrastination in students who join organizations, and to find out more about the relationship between time management and academic procrastination in students who join organizations. This study uses a quantitative approach with a descriptive correlational type. The sample determination method uses the Total Sampling technique with 117 DPH UKM respondents. Data collection in this study uses a time management and academic procrastination scale. Data are processed using descriptive analysis techniques with percentage formulas and correlational analysis techniques with Pearson Product Moment. The results of the study show that: (1) academic procrastination of students who join organizations is in the moderate category (59.83%), (2) time management of students who join organizations is in the moderate category (50.43%), (3) there is a negative and significant relationship between time management and academic procrastination in students who join organizations. The implications of BK services are that they can provide information services on the theme of the importance of self-confidence in learning, individual counseling services, and group guidance services on the topic of assignments regarding self-confidence in learning.